Development of Liposomal Forms of Modified Pyrimidine Nucleosides and Investigation of Their Antibacterial Properties - I. L. Karpenko; G. M. Sorokoumova; I. G. Sumarukova; S. K. Gaydukevich; M. A. Zaretskaya; Q. V. Efremenkova; L. A. Alexandrova (Антибиотики и Химиотерапия)
Different phosphocholine-cardlolipin-2'-deoxyuridine inclusion complexes were developed, that allowed to compose a water-soluble form of nucleoside analogues with previously defined antituberculosis activity. It was found that the resulting liposomes effectively penetrated to the cells. The increase of cytotoxicity was undoubtedly indicative of accumulation of the nucleoside in the cell culture. The result proved the ability of the liposomes for delivery of the low-soluble compounds to the cells for further investigation of their efficacy. It was shown that treatment of the bacterial cells with the liposomes of the modified nucleosides did not affect the bacterial growth.